EFEKTIVITAS PERMAINAN CERITA BERGILIR (STORY CHAIN) DALAM MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INDONESIA PADA SISWA KELAS IV SD INPRES ANA’GOWA KABUPATEN GOWA - Afrianty, Nur Hasana; Adam, Andi; Ratnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to test the effectiveness of the Story Chain game in improving the Indonesian language speaking skills of fourth-grade students at SD Inpres Ana'Gowa. This research is an experimental study with a quantitative approach. The experimental design used in this study was a pre-experimental design with one group of subjects, namely One Group Pretest-Posttest. The sample used was 32 fourth-grade students at SD Inpres Ana'Gowa. Based on the research results, data analysis, and discussion, it can be concluded that the story chain game is effective in improving the Indonesian language speaking skills of fourth-grade students at SD Inpres Ana'Gowa, Gowa Regency. This can be seen from the comparison of the pretest and posttest results, where there was an increase in the average student score from 62.8 in the pretest to 80.5 in the posttest. In addition, there was an increase in the number of students in the high and very high categories after the implementation of the story chain game in the learning process. The results of the inferential statistical analysis using the Wilcoxon Signed Rank Test also showed a significance value of Asymp. Significant difference (2-tailed) < 0.05